Insulin resistance and hyperinsulinemia in individuals with small, dense low density lipoprotein particles. - Reaven, G M (1993)
Subjects characterized by a predominance of small LDL particles (pattern B) have changes in plasma triglyceride (TG) and HDL-cholesterol concentrations consistent with the presence of resistance to insulin-mediated glucose uptake. To pursue this issue, plasma glucose and insulin responses to oral glucose, insulin-mediated glucose disposal, and lipoprotein concentrations were measured in subjects categorized on the basis of LDL peak diameter measured by gradient gel electrophoresis. Subjects with pattern B had higher (P < 0.05-0.001) total integrated plasma glucose (20.7 +/- 1.0 mmol/liter.h) and insulin (1,743 +/- 293 pmol/liter.h) responses to oral glucose compared with glucose (16.3 +/- 0.4 and 19.2 +/- 0.8 mmol/liter.h) and insulin (856 +/- 60 and 1,222 +/- 168 pmol/liter.h) responses in those with either pattern A or an intermediate pattern. Pattern B individuals were shown to be more insulin resistant on the basis of higher steady state plasma glucose concentrations (SSPG, 10.4 +/- 1.0, P < 0.002, vs. 7.5 +/- 0.7 and 6.0 +/- 0.4 mmol/liter) after a constant infusion of somatostatin, glucose, and insulin than those with either the intermediate or pattern A subclass. Pattern B subjects also had higher concentrations of (P < 0.001) TG (1.98 +/- 0.15 vs. 1.33 +/- 0.17 and 0.77 +/- 0.05 mmol/liter) and lower (P < 0.01-0.001) HDL cholesterol (1.12 +/- 0.06 vs. 1.34 +/- 0.05 vs. 1.45 +/- 0.05 mmol/liter) than those with either the intermediate or pattern A. Finally, significant (P < 0.001) correlation coefficients existed between LDL diameter and SSPG (r = -0.44); glucose (r = -0.41) and insulin (r = -0.38) responses; TG (r = -0.65) and HDL-cholesterol (r = 0.42) concentrations; and systolic (r = -0.34) and diastolic (r = -0.34) blood pressure. Thus, pattern B subjects are insulin resistant, have higher glucose, insulin, and TG, lower HDL-cholesterol levels, and higher blood pressure than those with pattern A or intermediate.